Siegfried Sassoon correspondence - Sassoon, Siegfried, 1886-1967.
ALS written by Sassoon to Joseph Auslander enclosing an autograph copy of Sassoon's poem, Everyone Sang, composed in 1919.
British author and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Auslander, Joseph, -- 1897-1965 -- Correspondence